Steady-state performance assessment and geometrical optimization of packed-bed liquid desiccant air dehumidification systems. (1st February 2023) - Bhowmik, Mrinal; Gohain, Karanjeet; Muthukumar, P.; Saito, Kiyoshi
Graphical abstract: Highlights: Cross flow and counter flow adiabatic packed bed dehumidifier is comparatively investigated. Three different halide desiccants are studied: LiCl/H2 O, LiBr/H2 O and HCOOK/H2 O. LiCl/H2 O and HCOOK/H2 O provided the highest and lowest dehumidification performance, respectively. Maximum dehumidification effectiveness is found to be around 75%. Trade-off analysis and correlation matrix heatmap are discussed for the liquid desiccant system. Abstract: In the present study, the performance of the liquid desiccant dehumidifier is numerically investigated under different flow configurations using commercially available halide solutions. For this purpose, a steady-state numerical model is developed for analysing the heat and mass transfer characteristics between air and solution by considering moist air properties and validated with experimental datasets. The dehumidification performance is assessed by the moisture effectiveness and moisture removal rate, while its latent load-controlling performance is evaluated by the latent heat ratio. The effect of geometric parameters on the dehumidifier's performance is also studied. The results showed that a dehumidifier with a cross-flow configuration performed better than the counter-flow for the same dehumidifier volume. Further, the dehumidifier with lithium chloride solution showed the highest performance among the investigated systems. It is also found that geometric parameters for both counter and cross-flow dehumidifiers played a major role in defining the performance of the dehumidifier. Lastly, trade-off contours and correlation matrix are mapped to analyze the relative influence of the system's independent variables on the dehumidifier's performance.